Characterization, pharmacokinetics, and hypoglycemic effect of berberine loaded solid lipid nanoparticles - Xue M (Dove Medical Press, 2013)
Mei Xue, Ming-xing Yang, Wei Zhang, Xiu-min Li, De-hong Gao, Zhi-min Ou, Zhi-peng Li, Su-huan Liu, Xue-jun Li, Shu-yu Yang Xiamen Diabetes Institute, The First Affiliated Hospital of Xiamen University, Xiamen, People’s Republic of China Abstract: The high aqueous solubility, poor permeability, and absorption of berberine (BBR) result in its low plasma level after oral administration, which greatly limits its clinical application. BBR solid lipid nanoparticles (SLNs) were prepared to achieve improved bioavailability and prolonged effect. Developed SLNs showed homogeneous spherical shapes, small size (76.8 nm), zeta potential (7.87 mV), encapsulation efficiency (58%), and drug loading (4.2%). The power of X-ray diffraction combined with 1H nuclear magnetic resonance spectroscopy was employed to analyze chemical functional groups and the microstructure of BBR-SLNs, and indicated that the drug was wrapped in a lipid carrier. Single dose (50 mg/kg) oral pharmacokinetic studies in rats showed significant improvement (P<0.05) in the peak plasma concentration, area under the curve, and variance of mean residence time of BBR-SLNs when compared to BBR alone (P<0.05), suggesting improved bioavailability. Furthermore, oral administration of both BBR and BBR-SLNs significantly suppressed body weight gain, fasting blood glucose levels, and homeostasis assessment of insulin resistance, and ameliorated impaired glucose tolerance and insulin tolerance in db/db diabetic mice. BBR-SLNs at high dose (100 mg/kg) showed more potent effects when compared to an equivalent dose of BBR. Morphologic analysis demonstrated that BBR-SLNs potentially promoted islet function and protected the islet from regeneration. In conclusion, our study demonstrates that by entrapping BBR into SLNs the absorption of BBR and its anti-diabetic action were effectively enhanced. Keywords: berberine, solid lipid nanoparticles, pharmacokinetic, hypoglycemic effect